Effect of Different Fertilizer Management on Soil Properties and Yield of Fine Rice Cultivar - Islam, MR; Sikder, S; Bahadur, MM; Hafiz, MHR (Journal of Environmental Science and Natural Resources, 2012)
The experiment was conducted at the Research Farm of Crop Physiology and Ecology Department, Hajee Mohammad Danesh Science and Technology University, Dinajpur during 14 August to 7 December, 2008 to study the effect of (different organic and inorganic) fertilizer management on soil properties and yield of five fine rice cultivars viz., Rajshahi swarna, Silkumul, Kataribhog, Lal pajam and Sanla. The experiment was laid out in a split plot design with three replications. For post harvest soil, bulk density and pH gradually decreased in organic fertilizer management compared to inorganic fertilizer management. But percent organic carbon (0.68 to 0.80%) and organic matter (1.19 to 1.37%) of soil increased in organic management compared to inorganic management (0.53 to 0.66% and 0.91 to 1.14%, respectively). All the cultivars gave some-what better yield under inorganic management where the yield variation was minimum between organic and inorganic management. Conversely, organic culture had beneficial effects in improving soil properties and the sustainable agriculture mostly depends on soil organic matter. This organic matter will remain stable by using organic fertilizer. DOI: http://dx.doi.org/10.3329/jesnr.v5i1.11588 J. Environ. Sci. & Natural Resources, 5(1): 239-242, 2012